Effects of DAPAgliflozin on CARDiac substrate uptake, myocardial efficiency, and myocardial contractile work in type 2 diabetes patients—a description of the DAPACARD study - Axel Åkerblom; Jonas Oldgren; Aino Latva-Rasku; Lars Johansson; Vera Lisovskaja; Cecilia Karlsson; Jan Oscarsson; Pirjo Nuutila (Taylor and Francis Ltd, 2022)
Background: Diabetes increases the risk for cardiovascular (CV) events. It has recently been shown that the use of sodium-glucose cotransporter 2 (SGLT2) inhibitors leads to a reduction in CV outcomes in patients with type 2 diabetes mellitus (T2DM), including mortality and heart failure hospitalization. The exact mechanisms of how SGLT2 inhibitors lead to this CV risk reduction remain incompletely understood. The study of DAPAgliflozin on CARDiac substrate uptake, myocardial efficiency and myocardial contractile work in type 2 diabetes patients (DAPACARD) (NCT03387683) explores the possible effects of dapagliflozin, an SGLT2 inhibitor, on cardiac work, metabolism, and biomarker levels.
Methods: DAPACARD is an international, randomized, double-blind trial that aims to examine the effects of dapagliflozin versus matching placebo in 52 patients with T2DM that are on stable metformin therapy prior to and during the 6 weeks of treatment. The primary efficacy endpoint is change in global longitudinal strain of the left ventricle (GLSLV) measured with magnetic resonance imaging (MRI) between baseline (pre-treatment) and end of study (on-treatment). The secondary endpoint is the corresponding change in myocardial efficiency measured as external left ventricular work divided by total left ventricular work, which is estimated using [11C]-acetate clearance using positron emission tomography (PET).
Conclusion: The DAPACARD study is an extensive investigation of cardiac function and metabolism, by advanced imaging with PET and MRI, as well as biomarkers, performed in order to further explore how the SGLT2 inhibitor dapagliflozin could influence cardiovascular outcomes in patients with T2DM.